PEDAGOGICAL CONDITIONS FOR USING AI PLATFORMS TO FOSTER STUDENTS’ LEARNING AUTONOMY (World Bulletin of Education and Learning, 2025)
This article examines the pedagogical conditions for the effective use of artificial intelligence (AI) platforms in fostering students’ learning autonomy. The study focuses on the role of AI-based educational technologies in supporting independent learning, self-regulation, and personalized educational pathways. Methodologically, the research is based on qualitative analysis, including a review and comparison of relevant pedagogical and technological literature. The findings indicate that the successful integration of AI platforms into the educational process requires the alignment of pedagogical objectives, adaptive learning models, and continuous feedback mechanisms. The study highlights that AI platforms contribute to the development of students’ cognitive independence, motivation, and responsibility for learning outcomes. Overall, the research substantiates the pedagogical potential of AI platforms in enhancing students’ learning autonomy in higher education.
Keywords: Artificial intelligence, AI platforms, learning autonomy, pedagogical conditions, independent learning, higher education, adaptive learning.